Robust electrochemical metal oxide deposition using an electrode with a superhydrophobic surface. Issue 1 (8th December 2016) - Zhang, Jun; Sheng, Xia; Cheng, Xiqing; Chen, Liping; Jin, Jian; Feng, Xinjian
Abstract : Described herein is the robust metal oxide deposition on an electrode with a superhydrophobic surface. Abstract : Described herein is the first study of metal oxide deposition on an electrode with a solid/liquid/gas triphase reaction interface. Such an electrode enables the formation of a locally high interface pH value that is independent of the bulk conditions, and allows the deposition of a wide variety of metal oxides in a robust electrolyte. The results reveal that the control of electrode surface wettability is of significant importance for the regulation of the electrode–electrolyte local interface environment, which provides a new set of guidelines and perspective for future electrode preparation and application.